2021
DOI: 10.1007/s10995-021-03272-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Health Care, Information, and Social Support Among Women Affected by Zika Virus Infection During Pregnancy in Two U.S. States

Abstract: Objectives To understand the information needs and experiences with health care and social support among women with confirmed or possible Zika virus infection during pregnancy. Methods We conducted in-depth interviews with 18 women whose pregnancies were part of surveillance efforts in two states, Pennsylvania and Virginia. Using a semi-structured guide available in English and Spanish, we asked women about their experiences. We conducted a thematic analysis using NVivo 11. Results Only one participant reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…The above reports of mothers corroborate the findings of other investigations, which believe that such mothers may be a vulnerable group to develop mental health problems, such as depression, stress and anxiety (Kuper et al, 2019;Ornelas Pereira et al, 2020;Santos, Tavares, et al, 2021;Squiers et al, 2021). Such symptoms may be related to these mothers' uncertainties and challenges regarding their children, their journeys, a worse perception of personal competence, triggering psychological distress and worse quality of life in mothers of children with microcephaly (Santos, Tavares, et al, 2021;Squiers et al, 2021), as we found in this study.…”
Section: Quality Of Life Of Mothers Of Children With Microcephalysupporting
confidence: 92%
“…The above reports of mothers corroborate the findings of other investigations, which believe that such mothers may be a vulnerable group to develop mental health problems, such as depression, stress and anxiety (Kuper et al, 2019;Ornelas Pereira et al, 2020;Santos, Tavares, et al, 2021;Squiers et al, 2021). Such symptoms may be related to these mothers' uncertainties and challenges regarding their children, their journeys, a worse perception of personal competence, triggering psychological distress and worse quality of life in mothers of children with microcephaly (Santos, Tavares, et al, 2021;Squiers et al, 2021), as we found in this study.…”
Section: Quality Of Life Of Mothers Of Children With Microcephalysupporting
confidence: 92%